Building Success in Change Across Diverse Stakeholders Understanding the Human Side of Digital Tool Implementation in Construction Projects - Brusbo, Moa; Gryte, Elin (My University, 2025)
Digitalization is reshaping industries, yet the construction sector continues to face challenges due to fragmented workflows, rigid systems, and a culture of slow adoption. To realize the full potential of digitalization, organizations must understand individual motivation and offer trust-based support throughout the change process to ensure successful implementation. This study presents a case at Skanska, a leading construction company, focusing on the implementation of two digital tools: ACC and SAI. These tools were selected for their contrasting outcomes; ACC was perceived as a successful implementation, while SAI was seen as less successful, offering valuable insights when analyzed alongside change management theory and an individual perspective. Data was collected through semi-structured interviews with both implementers and recipients, complemented by on-site observations. The results show that wellprepared implementations fostered alignment between stakeholders and increased user motivation, while rushed rollouts led to confusion, resistance, and lower adoption. This thesis emphasizes that digital transformation is not merely a technical challenge, but a human and organizational one. Our findings highlight the importance of early user involvement, emotional acknowledgment, and the relationship between implementers and recipients. By focusing on the emotional and strategic aspects of the preparatory phase, we offer new insights into how genuine engagement can drive successful digital implementation.
Keywords: Change Management; Implementation; Digital Transformation; Construction Industry; Leadership; Bottom-up Approach; Employee Empowerment; Involvement; Diverse Stakeholders